2022
DOI: 10.1155/2022/3859155
|View full text |Cite
|
Sign up to set email alerts
|

A Metaheuristic Autoencoder Deep Learning Model for Intrusion Detector System

Abstract: A multichannel autoencoder deep learning approach is developed to address the present intrusion detection systems’ detection accuracy and false alarm rate. First, two separate autoencoders are trained with average traffic and assault traffic. The original samples and the two additional feature vectors comprise a multichannel feature vector. Next, a one-dimensional convolution neural network (CNN) learns probable relationships across channels to better discriminate between ordinary and attack traffic. Unaided m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Pandey et al [ 18 ] developed a meta-heuristic autoencoder deep learning-based model for the intrusion detection system. A multichannel autoencoder deep learning approach was developed to determine the accuracy and false alarm rate of the intrusion detection systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pandey et al [ 18 ] developed a meta-heuristic autoencoder deep learning-based model for the intrusion detection system. A multichannel autoencoder deep learning approach was developed to determine the accuracy and false alarm rate of the intrusion detection systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The access of information helps in implementing the concern of the process. In one research (Pandey et al, 2022) it has been shown using advanced machine learning and Artificial Intelligence techniques, one can deter the intrusion threats. An effective Machine learning model can well simulate the customer behavior (Gunjan et al, 2022).…”
Section: Demeritsmentioning
confidence: 99%
“…As WSN networks expand in both scale and user base, they generate traffic data with high-dimensional characteristics, presenting challenges for conventional ML models in terms of feature extraction and detection accuracy. These limitations might not align with the specific demands of this application environment 10 . ML models, compare with traditional models, it can reduce computation burden and better learn the data traffic characteristics, leading to improved detection precision 11 .…”
Section: Introductionmentioning
confidence: 99%